Novel Natural Surfactant-Based Fatty Acids and Their Corrosion-Inhibitive Characteristics for Carbon Steel-Induced Sweet Corrosion: Detailed Practical and Computational Explorations - Abd El-Lateef, Hany M.; El-Beltagi, Hossam S.; Mohamed Mohamed, Maged Elsayed; Kandeel, Mahmoud; Bakir, Esam; Toghan, Arafat; Shalabi, Kamal; Tantawy, Ahmed H.; Khalaf, Mai M. (Frontiers in Materials, 2022)
Steel alloys are significant industrial substances, but they generally suffer severe corrosion under harsh conditions. Using inhibitors is an efficacious method to impede corrosion. So, in this study, two novel natural surfactants based on soybean oil have been synthesized by a facile route, namely, 1-(bis(2-hydroxyethyl)amino)-1-oxooctadecan-9-yl sulfate 2-hydroxyethan-1-aminium (CSM) and–N-(C2H4-OH)2; 1-(bis(2-hydroxyethyl)amino)-1-oxooctadecan-9-yl sulfate bis(2-hydroxyethyl)aminium (CSD), and their chemical structures were elucidated by physical–chemical approaches, Fourier transform infrared (FT-IR) spectroscopy, and surface activity measurements. The inhibitive effect of natural surfactants (CSM and CSD) on the C-steel corrosion in CO2-saturated 3.5% NaCl has been estimated in this investigation by electrochemical and surface analyses including electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), linear polarization resistance (LPR) corrosion rate, X-ray photoelectron spectroscopy (XPS), and field-emission scanning electron microscope/energy-dispersive X-ray spectroscopy (FESEM/EDX) approaches. The EIS study reveals the value of Rp augmented to an increase of 913.5 Ω cm2 with a protection capacity of 96.1% at 150 ppm (CSD). The outcomes of PDP suggested that CSM and CSD are mixed-type inhibitors. XPS and FESEM/EDX analyses determined the protective film formation on a metal interface having undamaged surface morphology and more homogeneities in the occurrence of the surfactant. Moreover, the adsorption of natural surfactants on the metal substrate takes place based on the model of Langmuir isotherm. Density functional theory (DFT) calculations and Monte Carlo (MC) simulations were selected for attaining basic atomic/electronic-scale details about the prepared surfactants, which support the practical findings. This study is intended to investigate the protection of C-steel using sweet service conditions with green extract surfactants.